A survey of the in vitro antifungal activity of heather (Erica sp.) organic honey - Feás, Xesús (2011)
Monofloral heather (Erica sp.) honey samples (n = 89), harvested in Portugal according to European organic beekeeping rules, were analyzed to test their antifungal effect against Candida albicans, Candida krusei, and Cryptococcus neoformans. A synthetic honey solution was also tested to determine antifungal activity attributable to sugars. The specific growth rate (l) values showed that growth of all the yeasts was reduced in the presence of honey. The honey concentration (% wt/vol) that inhibited 10% of the yeast growth (Xmin) was 13.5% for C. albicans, 20.5% for C. krusei, and 17.1% for C. neoformans. The respective concentrations of heather honey and synthetic honey in the C. krusei culture medium above 60% (wt/vol) that inhibited 90% of the yeast growth (Xmax) and Xmin, respectively, were established, whereas C. albicans and C. neoformans were more resistant because Xmax values were not reached over the range tested (10–60%, wt/vol). Heather honey might be tapped as a natural resource to look for new medicines for the treatment of mycotic infections. Further studies are now required to demonstrate if this antifungal activity has any clinical application.